What are the causes of the distressed state of the Highlands of Scotland? - Hancock, W. Neilson (Belfast Social Inquiry Society, 1852)
It will not be necessary for me to occupy much of your time in adducing evidence of the nature and extent of the distressed state of the poorer classes in the Highlands of Scotland. To account for this distress, many of the theories put forward with respect to Ireland have been urged with more or less favour in Scotland ; such as, the Celtic race, the potato, absenteeism, overpopulation, and want of capital. As, however, the Highlanders are an agricultural population, before adopting any of these solutions of the question, it seems natural to inquire what is the state of agriculture in the districts where this distress prevails. This inquiry is the more important, as in other parts of Scotland prosperous agriculture is attended, as we might expect, by a total absence of general distress.
A paper read before the Society on the 10th February, 1852
Keywords: Poverty; Scotland; Highlands; 314.15